Human–Pig Chimeric Organ in Organ Transplantation from Islamic Bioethics Perspectives - Mohd Zailani, Muhammad Faiq; Hamdan, Mohammad Naqib; Mohd Yusof, Aimi Nadia (Asian bioethics review, 2023)
The use of pig derivatives in medicine is forbidden in Islamic law texts, despite the fact that certain applications offer medical advantages. Pigs can be one of the best human organ hosts; therefore, using human–pig chimeras may generate beneficial impact in organ transplantation, particularly in xenotransplantation. In Islam, medical emergencies may allow some pig-based treatments and medical procedures to be employed therapeutically. However, depending on the sort of medical use, emergency situation might differ. Using Islamic legal maxim as bioethical framework, the purpose of this study is to examine the use of pigs for the purpose of human–pig chimeric transplant from the perspective of Islamic bioethics. According to the findings, chimeric organ transplantation using pigs should only be done in emergency situations.